1992
DOI: 10.1073/pnas.89.4.1398
|View full text |Cite
|
Sign up to set email alerts
|

Early molecular events in the induction phase of contact sensitivity.

Abstract: To assess changes in epidermis-derived cytokine mRNA levels early in the afferent phase of allergic contact sensitivity, total epidermal mRNA was analyzed at various times after painting skin with haptens. We used a sensitive reverse transcriptas-polymerase chain reaction technique to quantitatively compare the regulation patterns of the following mRNAs: class H major histocompatibility complex I-Aa, tumor necrosis factor a (TNF-a), interleukin (IL) la, IL-1l, interferon (IFN) y, granulocyte/macrophageoolonyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
312
4
6

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(342 citation statements)
references
References 27 publications
20
312
4
6
Order By: Relevance
“…Our data confirm and extend data recently reported by others [16,17,36,37] in that this study specifically deals with cutaneous aspects of migration: first, we observe a dose-dependent differential effect of TNF-␣ on DC migration (enhancement by low doses/ inhibition by high doses). Second, we extend the description of cytokine influence on migration to the dermal compartment (effect of cytokines on migration within dermal lymphatics).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our data confirm and extend data recently reported by others [16,17,36,37] in that this study specifically deals with cutaneous aspects of migration: first, we observe a dose-dependent differential effect of TNF-␣ on DC migration (enhancement by low doses/ inhibition by high doses). Second, we extend the description of cytokine influence on migration to the dermal compartment (effect of cytokines on migration within dermal lymphatics).…”
Section: Discussionsupporting
confidence: 81%
“…There, the cytokines are not accessible to measurement by ELISA. In the model of murine contact hypersensitivity it has been shown that mRNA for both cytokines is expressed in the epidermis on application of a contact sensitizer and concomitant with the emigration of Langerhans cells from the epidermis [37]. The same was found in a murine model of heart transplantation [43], where DCs also migrate out of the organ [44].…”
Section: Cytokines In Skin Explant Culturessupporting
confidence: 52%
“…With respect to the source of dectin-1 mRNA expression, depletion of the Ia ϩ epidermal cell population (i.e. Langerhans cells) abrogated almost completely dectin-1 mRNA, as well as IL-1␤ mRNA, which is known to be expressed exclusively by Langerhans cells in murine epidermis (18,55,56). This corroborates our observations that dectin-1 mRNA was detected by Northern blotting in the XS52 Langerhans cell-like line, but not in cell lines derived from other epidermal cell populations, i.e.…”
Section: Identification Of Novel Genes Expressed By Xs52 DC Line Bymentioning
confidence: 99%
“…An additional selective role for IL-1[3 has been proposed in the development of contact hypersensitivity responses in the skin (25,26). Contact sensitizers increase the levels of mRNA for several cytokines in the skin, including IL-lct, IL-113, and TNFcx.…”
mentioning
confidence: 99%